Oxalate as a potent promoter of kidney stone formation - Chen, Tao; Qian, Biao; Zou, Junrong; Luo, Peiyue; Zou, Jun; Li, Wei; Chen, Qi; Zheng, Liying (Frontiers in Medicine, 2023)
Kidney stones are among the most prevalent urological diseases, with a high incidence and recurrence rate. Treating kidney stones has been greatly improved by the development of various minimally invasive techniques. Currently, stone treatment is relatively mature. However, most current treatment methods are limited to stones and cannot effectively reduce their incidence and recurrence. Therefore, preventing disease occurrence, development, and recurrence after treatment, has become an urgent issue. The etiology and pathogenesis of stone formation are key factors in resolving this issue. More than 80% of kidney stones are calcium oxalate stones. Several studies have studied the formation mechanism of stones from the metabolism of urinary calcium, but there are few studies on oxalate, which plays an equally important role in stone formation. Oxalate and calcium play equally important roles in calcium oxalate stones, whereas the metabolism and excretion disorders of oxalate play a crucial role in their occurrence. Therefore, starting from the relationship between renal calculi and oxalate metabolism, this work reviews the occurrence of renal calculi, oxalate absorption, metabolism, and excretion mechanisms, focusing on the key role of SLC26A6 in oxalate excretion and the regulatory mechanism of SLC26A6 in oxalate transport. This review provides some new clues for the mechanism of kidney stones from the perspective of oxalate to improve the understanding of the role of oxalate in the formation of kidney stones and to provide suggestions for reducing the incidence and recurrence rate of kidney stones.